2021
DOI: 10.1016/j.apsb.2021.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing carrimycin as an antiviral agent against human coronaviruses, including the currently pandemic SARS-CoV-2

Abstract: COVID-19 pandemic caused by SARS-CoV-2 infection severely threatens global health and economic development. No effective antiviral drug is currently available to treat COVID-19 and any other human coronavirus infections. We report herein that a CFDA-approved macrolide antibiotic, carrimycin, potently inhibited the cytopathic effects (CPE) and reduced the levels of viral protein and RNA in multiple cell types infected by human coronavirus 229E, OC43, and SARS-CoV-2. Time-of-addition and pseudotype virus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Repurposing old drugs in treating other diseases is a technique with many advantages including time and cost savings, since the safety and toxicity of candidate drugs have already been clearly studied [17]. Carrimycin is a Chinese Food and Drug Administration (CFDA)-approved macrolide antibiotic [32]. Here, we firstly isolated the active component of carrimycin, ISP-I, and verified its satisfying anti-NSCLC effect both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Repurposing old drugs in treating other diseases is a technique with many advantages including time and cost savings, since the safety and toxicity of candidate drugs have already been clearly studied [17]. Carrimycin is a Chinese Food and Drug Administration (CFDA)-approved macrolide antibiotic [32]. Here, we firstly isolated the active component of carrimycin, ISP-I, and verified its satisfying anti-NSCLC effect both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, carrimycin ( 14 ) was approved by NMPA for pneumonia treatment in 2019. Of note, carrimycin ( 14 ) displays a broad-spectrum antiviral activity against human coronaviruses, including COVID-19, and is preferentially distributed in the lungs by oral administration 161 . As a result, several clinical trials are currently under way to investigate the efficacy of carrimycin ( 14 ) against COVID-19.…”
Section: Carbohydrate-based Antibacterial and Antiparasitic Drugsmentioning
confidence: 99%
“…Previous studies found that carrimycin exerts efficacy after the virus enter cells, which can reduce the newly synthesized RNA level of coronavirus, indicating that carrimycin can play an anti-coronavirus role by affecting coronavirus RNA replication. In addition, Carrimycin can regulate the interferon signaling pathway JAK/stat, ISGS, and PI3K Akt mTOR signaling pathway 15 . A phase Ⅲ clinical trials of carrimycin in hospitalized patients with severe COVID-19 have been completed.…”
Section: Small-molecule Drugsmentioning
confidence: 99%